Ritmo e poesia nos duelos da vida: levante denunciante, ritmo dançante e educação participante: improvisações etnográficas acerca da cultura Hip Hop e da performance do Duelo de Mcs - Flávia Goodwin Gomes (2015)
Addressing lifes duels, this research aims at developing ethnographic improvisations in the mist of Social Anthropology concerning the sharing of performances and narrations (ou narr- actions) that engender new ways of acting on political and social insertion of excluded individuals. The focus of this research was the promotion of the encounter and the learning, established through experience and participation, from within and from nearby. Therefore, the motto was the contact with the hip hop culture, which consists basically of a collective manifestation of the urban marginalized youth. A movement that reveals itself based on aesthetic-political expressions and private intentions, such as self assertion, criticality, behavior and anti-cordiality. The ethnographic contact was established from the experiencing of the Duelo de Mcs, from where emerges the freestyle: improvised rhymes in free style. Such performances are able to trigger practical learning, the sharing of the sensible and install liminoid moments of conversion of the senses and common feelings. According to this conception, hip hop, observed through the battle performances, allows the building of our reading, supported by a tripod where Participant Education, Dancing Rhythm and Complainant Uprising constitute metaphors about the main characteristics of the production of this street culture.